2009
DOI: 10.1590/s1516-89132009000300017
|View full text |Cite
|
Sign up to set email alerts
|

Development and optimization of extractives from Astronium urundeuva (allemão) Engl. by factorial design

Abstract: The purpose of this study was to evaluate the influences from variables of preparation on dry residue and total tannins from macerates of Astronium urundeuva barks. Thus, a 3 2 factorial design was used to study the importance of plant proportion (10, 15 and 20 %, w/v) and the ethanol concentration (40, 60 and 80 %, v/v)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 8 publications
0
12
0
1
Order By: Relevance
“…Among these species, A. urundeuva is the most well-known due to its biological properties as some studies have described the presence of important components, including flavonoids, essential oils, and hydrolyzable and condensed tannins. 10 Some of the antiulcer effects of aqueous and alcoholic extracts of plants from the Astronium genus against experimental ulcers were observed in rats. More recently, other studies have shown antioxidant, antidiarrheal, anti-inflammatory, and analgesic effects.…”
Section: Introductionmentioning
confidence: 99%
“…Among these species, A. urundeuva is the most well-known due to its biological properties as some studies have described the presence of important components, including flavonoids, essential oils, and hydrolyzable and condensed tannins. 10 Some of the antiulcer effects of aqueous and alcoholic extracts of plants from the Astronium genus against experimental ulcers were observed in rats. More recently, other studies have shown antioxidant, antidiarrheal, anti-inflammatory, and analgesic effects.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the quadratic effect of L/S ratio was significant and negative ( Table 4). The contribution of the quadratic term is interpreted as the presence of a curve and represents the nature of the response surface system (maximum, minimum, or saddle point) [23]. Hence, the negative signal for the quadratic term reveals a convex curve, as was observed for the L/S ratio variable (Fig.…”
Section: Resultsmentioning
confidence: 82%
“…The quadratic term demonstrates the contribution of the factor to the presence of curvature, which can be observed in the response surface graphs, indicating the nature of the system for maximum and minimum values under optimal conditions. 11,17 The study of RSMs generated by quadratic models reveals critical points of the experimental field that can characterize the nature of the surface system (maximum, minimum or saddle). The behavior is result of the contributions of the second order terms and describes the presence of curvatures.…”
Section: Resultsmentioning
confidence: 99%
“…The extractive efficiency (EE) was determined by the relation of the contents of the metabolites of interest (polyphenol, gallic acid or ellagic acid) to the solid content (dry residue) obtained for the extracts, according to the equation below. 11…”
Section: Extractive Efficiencymentioning
confidence: 99%
See 1 more Smart Citation